Policetídeos isolados de Penicillium herquei - MARINHO, Anderson Nonato do Rosario (2013)
In this work we are reporting the isolation of polyketides citreoserine (1), emodin (2), janthinone (3), dihydrocitrinone (4) and citrinin H-1 (5). The compounds were isolated by chromatographic procedures and identified by spectral methods of NMR 1D and 2D and MS. The compounds 1, 2 and 3 were tested against promastigotes of Leishmania brasiliensis.